Evaluasi Kegiatan Corporate Social Responsibility (CSR) Terhadap Pengembangan Sosial Ekonomi Masyarakat Di PT. Holcim Indonesia Tbk. Pabrik Cilacap - Bambang Triyanto (JFRES Journal of Fiscal and Regional Economy Studies, 2022)
Program Corporate Social Responsibility (CSR) PT. Holcim Indonesia Tbk. Cilacap Factory is intended for residents who live around the factory and mine sites. This program aims to improve living standards and income levels and improve the education of citizens, especially at school age. CSR programs also open job opportunities for the surrounding community in order to provide benefits and improve welfare. In general, CSR formats and concepts have been implemented by PT. Holcim Indonesia Tbk. Cilacap Factory is a combination of community relations and community empowerment. The implementation of this can be seen from the company's policy involving stakeholders in determining the program to be implemented in the CSR program. This format and concept already have planning documents and strategies for achieving targets because it is able to establish and empower the community. Corporate Social Responsibility programs that have been implemented by companies in the socio-economic development of the community are Posdaya, Infrastructure, Education, Social, Culture, Religion, and Environment. Posdaya activities have provided benefits in the economic field in the form of additional family income whereas before CSR activities the average income per month is Rp. 1,068,000.00 per month, and after CSR increased to Rp. 1,372,000.00 per month, or an increase of 9.6 percent. Other programs that have provided benefits for the surrounding community are in the field of infrastructure where there has been an absorption of labor from ongoing projects, as well as the availability of transportation access that makes it easier for people to market production results.